EDUKASI LITERASI DIGITAL UNTUK MENINGKATKAN KEMAMPUAN SISWA SEKOLAH DASAR DALAM MENGGUNAKAN INTERNET SECARA BIJAK - Sudarti Ni Wayan (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2026)
The increasingly rapid development of information technology has had a significant impact on people's lives, including elementary school-aged children. Increasing use of the internet and digital devices among children is not always accompanied by adequate digital literacy skills. This situation has the potential to create various risks, such as exposure to negative content, the spread of false information, and even device addiction. This community service activity aims to improve elementary school students' understanding of digital literacy so they can use technology safely, wisely, and responsibly. The implementation method uses an educational approach through counseling, interactive lectures, discussions, educational games, simulations of healthy internet use, and evaluation using pretests and posttests. The activity was conducted with 98 students in grades IV–VI. The results showed an increase in students' understanding of the concepts of digital literacy, internet ethics, personal data security, and the ability to recognize accurate information. The average score of participants increased from 65 in the pretest to 88 in the posttest. Furthermore, students demonstrated high enthusiasm throughout the activity. This program demonstrates that digital literacy education from an early age can increase students' awareness of using digital media positively and responsibly. Keywords: digital literacy, elementary school, community service, healthy internet, digital education